2016
DOI: 10.1002/fuce.201500204
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Effectiveness Model and Its Implication for Performance Loss Due to Electrode Microstructural Degradation in Solid Oxide Fuel Cells

Abstract: The electrochemical performance of solid oxide fuel cells (SOFCs) is known to depend strongly on the electrode microstructure. Based on the electrochemical effectiveness model recently explored by the authors, this study proposes a theoretical model for the reduction of current generation performance due to microstructural degradation. The effects of the three‐phase boundary length (TPBL) and the effective ionic conductivity are predicted for three distinct operating regimes: low (<0.05), intermediate (0.5–2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…, ϕ T depends on the microstructural, dimensional, and property parameters, namely, λ normalt normalp normalb V , L , σ eff , and r tpb . Previous studies showed that ϕ T encountered during the operation of IT‐SOFCs generally falls in the range of 5–20 for the anode reaction layer (Ni/YSZ) and 0.5–2.5 for the cathode reaction layer (LSM/YSZ) . The distribution of i normalt normalr V () η inside the active reaction layer is shown for various ϕ T values in Figure , by assuming the symmetric Butler–Volmer reaction kinetics (α = 0.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, ϕ T depends on the microstructural, dimensional, and property parameters, namely, λ normalt normalp normalb V , L , σ eff , and r tpb . Previous studies showed that ϕ T encountered during the operation of IT‐SOFCs generally falls in the range of 5–20 for the anode reaction layer (Ni/YSZ) and 0.5–2.5 for the cathode reaction layer (LSM/YSZ) . The distribution of i normalt normalr V () η inside the active reaction layer is shown for various ϕ T values in Figure , by assuming the symmetric Butler–Volmer reaction kinetics (α = 0.5).…”
Section: Resultsmentioning
confidence: 99%
“…The accuracy of the modeling was validated by the good agreements between the results obtained by the effectiveness model and those by the microscale models which consider the detailed electrochemical reaction and electronic and ionic charge transport . This clearly indicates that Eqs.…”
Section: Theory and Calculationsmentioning
confidence: 99%
“…14 Further studies on modeling agglomerates and effectiveness factors in room-temperature fuel cells have refined and extended modeling and experimental approaches. [15][16][17][18][19][20][21][22][23] In solid oxide fuel cells, Costagmagna et al modeled the active functional catalyst layer using an effectiveness factor approach, where the modified Thiele modulus compared the ratio between rates of reaction and ionic charge transport through the active layer; 24 subsequently, Shin and Nam incorporated Butler-Volmer kinetics into the rate expression, 25 Baek et al used this framework to hypothesize performance degradation, 26 and Nam investigated the influence of various charge transfer coefficients. 27 Recently, effectiveness factor analysis has also been utilized in gas diffusion electrodes for CO 2 reduction to model agglomerates 28 and as part of the development of an analytical model of the catalyst layer.…”
Section: List Of Symbolsmentioning
confidence: 99%
“…In addition, a simple correlation equation was also proposed along with the correlation coefficients relevant to the symmetric Butler-Volmer reaction kinetics. Their model was successfully used for one-dimensional simulation of a single-cell SOFC [22] and the theoretical prediction of electrode microstructural effects [23,24].…”
Section: Introductionmentioning
confidence: 99%